Implementasi Algoritma Dijkstra Dalam Penentuan Jalur Terpendek Di Yogyakarta Menggunakan GPS Dan Qt Geolocation - Blasius Neri Puspika; Antonius Rachmat Chrismanto; Erick Kurniawan (Jurnal Informatika, 2013)
With the development of information technology, the map is no longer in the form of sheet or book. Currently there is a digital map services already invested in mobile devices. Google Maps is one of the leading providers of online digital map which can be accessed using the Application Programming Interface (API) is available using tools such as Qt. Qt is a C + + framework which provides a library to get the location using a GPS device to the library QtGeolocation. By implementing Dijkstra's algorithm, the problem of determining the shortest path towards a desired location of a user's location can be overcome. This study discusses how to implement the algorithm to find the shortest path Djikstra in Yogyakarta-based mobile devices.